Experimental and numerical study on the interface behaviour between the rock bolt and bond material - Yokota, Yasuhiro (2020)
Conventional tunnelling methods (i.e., the drill and blast tunnelling method or the new Austrian tunnelling method) have been frequently applied for the construction of tunnels/caverns under a high overburden and with a large cross section. Under such adverse conditions, tunnel support materials may yield because of ground pressure and tunnel deformation. As a result, a tunnel may lose its stability due to a reduced effectiveness of the tunnel supports. Rock bolts have been widely used as an essential component of tunnel support, and many studies have been conducted on the performance of rock bolts in strengthening the jointed rock mass. However, there is a lack of understanding on the interface behaviour between the rock bolt and the bond material, especially the crack initiation and propagation inside the bond material. This study aims to investigate the interface behaviour between rock bolts and bond materials using laboratory tests (shear tests) and numerical simulations (Discontinuous deformation analysis). By assessing the impact of the key parameters in the rock bolting system, such as the ribs, rib angle, strength of the bond material and the confining pressure, we are able to better understand the supporting mechanism and the effects of rock bolting.